Low temperature self-assembled synthesis of hexagonal plate-shape Mn3O4 3D hierarchical architectures and their application in electrochemical capacitors1. Issue 68 (25th July 2015) - Liu, Zhenxin; Xing, Yu; Fang, Shaoming; Qu, Xiongwei; Wu, Depeng; Zhang, Aiqin; Xu, Bei
<x xml:space="preserve">Abstract</x> Low temperature self-assembled synthesis of hexagonal plate-shape Mn3O4 3D hierarchical architectures and their application in electrochemical capacitors.